Dark and photofermentation H2 production from hydrolyzed biomass of the potent extracellular polysaccharides producing cyanobacterium Nostoc commune and intracellular polysaccharide (glycogen) enriched Anabaena variabilis NIES-2095. (21st June 2019) - Morsy, Fatthy Mohamed; Elbadry, Medhat; El-Sayed, Wael S.; El-Hady, Deia Abd
Abstract: The biological H2 production industry would be independent from other industries if it has its own supply of organic materials especially in non-agricultural countries. In this study, acid hydrolyzed biomass of the potent extracellular polysaccharides (EPSs) producing cyanobacterium Nostoc commune and glycogen (as intracellular polysaccharide) enriched Anabaena variabilis NIES-2095 were used as a cheap organic carbon feedstock for biological H2 production by two stages dark fermentation by Escherichia coli strain MWW and Clostridium acetobutylicum DSM-792 or Clostridium beijerinckii DSM-1820 and photofermentation by Rhodobacter capsulatus JCM-21090 under anaerobic conditions. Acid hydrolysis of air dried cyanobacterial biomass was conducted at optimum conditions of 4 M HCl at 120 °C in an autoclave for 30 min and subsequently neutralized and used as an organic carbon source for first stage dark fermentation followed by a second stage photofermentation. The facultative anaerobe Escherichia coli strain MWW was used for maintaining anaerobiosis. Escherichia coli strain MWW was isolated and identified by morphological and biochemical characterizations as well as molecular biological phylogenetic analysis of its 16S rDNA sequence. Nostoc commune was identified by morphological and microscopic characterizations and by 16S rDNA sequence phylogenetic analysis. The two stages dark fermentation by Escherichia coli and Clostridium acetobutylicum or Clostridium beijerinckii and photofermentation by Rhodobacter capsulatus produced in total 5.9 and 5.6 mol H2 /mole reducing sugars of acid hydrolyzed Nostoc commune EPSs/biomass, respectively and 5.43 and 5 mol H2 /mole reducing sugars of acid hydrolyzed biomass of glycogen enriched Anabaena variabilis, respectively. These results indicate a high potency of using cyanobacterial polysaccharides/biomass (extracellular polysaccharides and intracellular glycogen) as an organic carbon source for H2 production which would be of importance for non-agricultural countries. Graphical abstract: Image 1 Highlights: N. commune extracellular polysaccharides/biomass was efficient for H2 production. Intracellular glycogen enriched Anabaena biomass was efficient for H2 production. E. coli was used for maintaining anaerobiosis for H2 production by Clostridium . H2 production was efficiently conducted by two stages dark and photo-fermentation. Cyanobacterial polysaccharides would be useful for non-agricultural countries.